DEVELOPING WRITING STRATEGIES OF POOR LANGUAGE LEARNERS AT THE LEVEL OF JUNIOR-HIGH SCHOOL - Droździał-Szelest, Krystyna; Domińska, Mirosława Anna (Neofilolog, 2018)
Although language learning strategy research has been going on for almost forty years and has provided both theorists and practitioners with an abundant body of knowledge on the subject, there are still areas that need further investigation. One such area is the use of strategies in language skills development, with the skill of writing being singled out as deserving special attention. It is suggested that in order to better understand the processes involved, we need more information concerning the development of the skill by learners, as well as more data revealing the effects of strategy based instruction, especially with reference to children and adolescents in different foreign language learning contexts. Hence, this article makes an attempt to contribute to the ongoing discussion by focusing on a special group of learners – poor language learners, at a risk of educational failure – who are learning a foreign language (English) in the context of junior high school. The article consists of two parts: its theoretical sections focus on some issues related to poor language learners, with emphasis on factors impacting their school problems in general and learning of the writing skill in particular. Then, based on the literature review, some research findings concerning writing strategies and the effects of strategic training are discussed. The second part presents and comments on the data obtained during the course of an informal study carried out in a junior high school within the framework of an educational project which was remedial in character.